The Effect of Non-Thermal Plasma on the Structural and Optical Characteristics of SnO2:Co Thin Films Prepared by Spray Pyrolysis Technique - Randa Mohammed; Ramiz Ahmed Al- Ansari (Journal of Engineering)
This study used a spray pyrolysis approach to create thin films from SnO2 doped with 2% Co on a heated glass substrate at 400°C and investigated how the structural and optical characteristics are affected by non-thermal plasma. X-ray diffraction analysis was initially employed to look into the structural characteristics, and the results indicate that the SnO2 and SnO2:Co thin film are polycrystalline and have tetragonal structure, peak formation has occurred in (110), (101), and (211), which correlate to the subsequent diffraction angles, respectively (26.55⁰), (33.90⁰), and (51.55⁰). A peak associated with Co was also observed at (311), which is equivalent to the (36.78⁰) diffraction angle. According to AFM analysis, the grain size decreases from 64.01 nm to 59.10 nm after doping. Roughness and root mean square also appears to increase after doping, according to the UV-VIS spectrometer analysis, thetransmittance increases with doping and decreases with non-thermal plasma exposure, the energy gap value increases during Non-thermal plasma exposure and its decrease after doping. Additionally, the absorbance, absorbance coefficient, refractive index and extinction coefficient rise following Cold plasma exposure.